Reversed‐phase–high‐performance liquid chromatography method simultaneous quantification of Ivabradine hydrochloride and Bisoprolol fumarate. Issue 9 (26th June 2022) - Patel, Mansi M.; Chhalotiya, Usmangani K.; Shah, Dimal A.; Kachhiya, Hetaben M; Tandel, Jinal N.
Abstract: For the simultaneous quantification of Ivabradine hydrochloride and Bisoprolol fumarate in bulk and synthetic mixtures, a sensitive, precise, robust, and accurate reverse‐phase–high‐performance liquid chromatographic technique was developed and validated according to the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use Q2 (R1) guideline. The Phenomenex C‐18 column (250 × 4.6 mm 2, 5 m) was equilibrated with mobile phase acetonitrile: KH2 PO4 (30:70, v/v), pH 5.0 was adjusted with 1% orthophosphoric acid, the flow rate was maintained at 1 ml/min, and analysis was performed using a photodiode array detector. Note that, 279 nm was found to be the common detection wavelength for Ivabradine hydrochloride and Bisoprolol fumarate. As per the International Council for Harmonization of Technical Requirements for Pharmaceuticals for Human Use criteria, the technique was validated for linearity, precision, accuracy, and robustness, as well as the limit of detection and limit of quantitation. The linearity range of Ivabradine hydrochloride and Bisoprolol fumarate was found to be 5–40 and 2.5–20 μg/ml and correlation coefficients were 0.9988 and 0.9994, respectively. The mean percentage recovery of Ivabradine hydrochloride and Bisoprolol fumarate was found to be 99.83–101.87 and 99.46–101.62%, respectively. The present work represents the sensitive, accurate, precise, and reproducible reversed‐phase high‐performance liquid chromatography method for the simultaneous quantification of Ivabradine hydrochloride and Bisoprolol fumarate, and none of the liquid chromatography methods published on this novel combination. The proposed reversed‐phase high‐performance liquid chromatography method has potential qualitative as well as quantitative applications for simultaneous estimation of Ivabradine hydrochloride and Bisoprolol fumarate in bulk and synthetic mixture. Once pharmaceutical formulation comes into the market proposed reversed‐phase high‐performance liquid chromatography method is used for the qualitative and quantitative simultaneous estimation.